Sports science research and technology support : third International Congress, icSPORTS 2015, Lison, Portugal, November 15-17, 2015. Revised selected papers /: third International Congress, icSPORTS 2015, Lison, Portugal, November 15-17, 2015. Revised selected papers. (2016) - Unknown
No abstract available